The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4028/www.scientific.net/amr.807-809.539
|View full text |Cite
|
Sign up to set email alerts
|

Influence Factors on Removal of Cadmium by Montmorillonite Supported Nano Zero-Valent Iron

Abstract: The montmorillonite supported nanozero-valent iron material (MT-NZVI) was synthesized to remove cadmium (Cd). The results showed that the removal efficiency of MT-NZVI on cadmium was much higher than that of montmorillonite (MT), and the removal efficiency of MT-NZVI on cadmium reduced with the increase of the initial concentration and the pH value, but increased with the increase of the dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Clay minerals, as rich natural resources, have been used for the remediation of contaminated water, with similar advantages such as low cost, high availability, and high specific surface area [35]. Common clay minerals that have been used as substrates are mainly bentonite [36][37][38][39][40][41][42][43][44][45][46], montmorillonite [47][48][49][50][51][52][53][54][55], kaolin [37,40,53,[56][57][58][59][60][61], sepiolite [62][63][64], zeolite [65,66], and attapulgite [67]. Clay minerals attract contaminants to the surface, and the addition of nZVI particles multiplies the active sites and increases their activity [68,69].…”
Section: Clays and Aluminosilicate Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clay minerals, as rich natural resources, have been used for the remediation of contaminated water, with similar advantages such as low cost, high availability, and high specific surface area [35]. Common clay minerals that have been used as substrates are mainly bentonite [36][37][38][39][40][41][42][43][44][45][46], montmorillonite [47][48][49][50][51][52][53][54][55], kaolin [37,40,53,[56][57][58][59][60][61], sepiolite [62][63][64], zeolite [65,66], and attapulgite [67]. Clay minerals attract contaminants to the surface, and the addition of nZVI particles multiplies the active sites and increases their activity [68,69].…”
Section: Clays and Aluminosilicate Mineralsmentioning
confidence: 99%
“…The removal of Cu was studied by Uzum et al (2009), Liu et al, (2013), Chang et al (2014), J. Wang et al (2015), and Yang et al (2018), with a maximum reported yield of 886 mg/g nZVI by Chang et al (2014) [26,53,56,79,88]. Cd was studied by Pang et al (2013), Liu et al (2013), Z. Li et al (2018), and Shi et al (2019), and the maximum removal of 46 mg/g nZVI was determined by Z. Li et al[45,47,71,88].…”
mentioning
confidence: 99%